Optical properties of iron-doped lithium niobate crystal depending on iron content and temperature - Yukselici, M. H.; Bulut, D.; Omur, B. Can; Bozkurt, A. Asikoglu; Allahverdi, C. (WILEY-V C H VERLAG GMBH, 2014)
The optical properties of LiNbO3 crystals doped with iron at mol% between 0.015 and 0.1 were studied by optical absorption and Raman spectroscopies. The long wavelength tail below the fundamental absorption band is modeled by Urbach exponent assumed to be due to the tunneling of charged carriers through potential energy barrier bent by micro-electric field. We presume that non-uniform local charge distribution creates micro-electric field. Temperature dependence of the Fe2+ absorption band is reported over the range from 100 to 250 K. The Fe2+ absorption band at around 2.58 eV is red shifted at a rate of 4 x 10(-5) eVK(-1) as the temperature increases. We conclude that Li deficiency increases with iron, which sit on Li sites. (C) 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: iron doping; LiNbO3; optical properties; Raman spectroscopy; Urbach model; DEFECTS; PURE; Physics